2000
DOI: 10.1139/cjz-78-7-1243
|View full text |Cite
|
Sign up to set email alerts
|

Pollock and the decline of Steller sea lions: testing the junk-food hypothesis

Abstract: The decline of Steller sea lions (Eumetopias jubatus) in the Gulf of Alaska and the Aleutian Islands may be the result of them eating too much pollock (a gadid fish) instead of a more balanced and diverse diet containing fattier fishes, such as herring or sandlance. We sought to test this junk-food hypothesis by feeding six captive Steller sea lions (ages 0.9-4.5 years) only pollock or herring. All sea lions gained mass while eating herring. However, eating only pollock for short periods (11-23 d) caused the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 21 publications
2
91
1
Order By: Relevance
“…The energy density of prey plays a central role in the foraging ecology of at least some otariids (Rosen & Trites 2000, Staniland et al 2007). The energy density of pelagic potential prey for sea lions Otaria flavescens off Chubut Province is much higher than that of the benthic potential prey (present study), so sea lions might be expected to show a preference for pelagic prey if energy density were the only criteria for prey selection.…”
Section: Discussionmentioning
confidence: 99%
“…The energy density of prey plays a central role in the foraging ecology of at least some otariids (Rosen & Trites 2000, Staniland et al 2007). The energy density of pelagic potential prey for sea lions Otaria flavescens off Chubut Province is much higher than that of the benthic potential prey (present study), so sea lions might be expected to show a preference for pelagic prey if energy density were the only criteria for prey selection.…”
Section: Discussionmentioning
confidence: 99%
“…Fasting may also have biased our estimates of food requirements in the opposite direction. A study on captive Steller sea lions showed that juveniles had the ability to depress their metabolic rate during periods of reduced energy intake (Rosen & Trites 1999, 2000b. If fasting adult females have a depressed metabolic rate then we would have overestimated food requirements.…”
Section: Food Requirements Of Individualsmentioning
confidence: 99%
“…This explanation of harbor seal population crashes, along with other marine mammals, has been highly controversial (Trites et al 2007a, Wade et al 2007). The alternative hypothesis for the decline of marine mammal populations involves bottom-up mediation through regime shifts and over-harvest of fisheries (Trites et al 1997, Francis et al 1998, Rosen & Trites 2000, Trites & Donnelly 2003, Trites et al 2007b). Bottom-up population control usually occurs through nutritional stress caused by limited prey availability or poor diet quality (Power 1992).…”
Section: Introductionmentioning
confidence: 99%